The impact of oral health literacy on oral health in lung cancer patients: the mediating role of psychosocial factors - Nan Zhang; Yingao Liu; Tiane Fa (Frontiers in Public Health, 2026)
Background Lung cancer patients often have poor oral health due to treatment toxicities, increasing risks of oral mucositis, and pulmonary infection. Oral health literacy (OHL) is a key determinant, and psychosocial factors such as anxiety and family support also play roles. However, prior studies examined only single dimensions, not underlying mechanisms. This study aims to build a mediation model linking OHL, psychosocial factors, and oral health status in lung cancer patients, providing exploratory evidence for potential targets (i.e., OHL and psychosocial factors) that may warrant attention during antitumor therapy. Methods This study recruited 250 lung cancer patients from a tertiary hospital in China to participate in a questionnaire survey. The study was conducted on a voluntary, anonymous basis, assessing patients’ general demographic information, relevant risk factor scales, the HeLD-14, oral health (BOAS, HBS, and OHIP-14), and psychosocial factors (PSS-Fa, SAS, and C-SUPPH). Finally, structural equation modeling was used to explore the interaction pathways among these three factors. Results The oral health status score for lung cancer patients was (9.14 ± 1.94) points, the oral health literacy score was (28.07 ± 5.39) points. Notably, oral health status among lung cancer patients was significantly positively correlated with both oral health literacy ( r = 0.389, p < 0.001) and psychosocial factors ( r = 0.402, p < 0.001). Furthermore, psychosocial factors were significantly positively correlated with oral health literacy ( r = 0.333, p < 0.001). Importantly, psychosocial factors partially mediated the relationship between oral health literacy and oral health status in lung cancer patients, with an indirect effect size of 0.264 (95% CI : 0.106–0.351), accounting for 49.70% of the total effect. Conclusion Psychosocial factors partially mediate the relationship between oral health literacy and oral health status. These findings suggest a potential pathway linking OHL to oral health status through psychosocial factors. From a clinical perspective, addressing both OHL and psychosocial factors may be a reasonable strategy to support oral health in lung cancer patients, although the cross-sectional design warrants cautious interpretation. Prospective studies are needed to confirm these relationships before firm clinical recommendations can be made.